Perencanaan Drainase di Dusun 1 Penfui Timur - Sri Santi L. M. F. Seran; Yohanes E. P. Paus; Fredy Saunoah; Grasiana da Silva; Arkadius Lelo (Local Engineering, 2023)
Drainage functions as a series of waterworks that function to reduce or remove excess water from an area or land, so that the land can function optimally. Hamlet 1 is one of the hamlets in East Penfui Village, with an area of 49.47 ha. This hamlet is quite busy with students living because it is located between 2 major campuses in Kupang, namely Nusa Cendana University and Widya Mandira Catholic University Kupang. This hamlet has not been equipped with adequate drainage channels so that during the rainy season there are floods and result in standing water at several points which is quite disturbing to road users and the surrounding community. Therefore, it is necessary to know the magnitude of the planned discharge so that it can determine the dimensions of the channel to overcome the problem of inundation that occurs. From the results of planning the drainage system is divided into 2 primary canals with the notation SP1 and SP2, the P1 channel is 2300 m long and the P2 channel is 600 m long. Calculating the intensity of rainfall using the mononobe formula, with a concentration time of 3.16 hours, the rainfall intensity for the 5 year return period is 30.74 mm. By using the rational method, it is obtained that the planned debit is 2.67 m3/s, in the planning of the drainage system there must be different channel dimensions based on the water discharge flowing through the channel itself. With a planned flood discharge of 24.75 m3/s, the smallest canal has a width dimension of 0.4 m and a height of 0.8 m on the secondary channel while the largest is 0.6 m wide and 1.2 m high on the primary canal, and Infiltration wells have a diameter of 2 m with a depth of. Provided that Q plan < channel discharge. Drainage planning uses a square-shaped channel with precast concrete materials, namely U-ditch channels and calvert box culverts.